EFFECTS OF INTERNAL CONTROL SYSTEM ON THE ORGANIZATOINAL PERFORMANCE OF REMITTANCE COMPANIES IN MODADISHU-SOMALIA - MIRE, HASSAN ADAM; Mukhongo, aaron (IJRDO - Journal of Business Management, 2016)
The purpose of this research would be to examine the effect of internal controlsystem practice on the performance of remittance companies in Mogadishu-Somalia. The studywould adopt a quantitative research with the specific research design being a descriptive design.The population of the study is the classified remittance companies locate in Bakara market, andthey were 15 remittance companies in Bakara market, the employees worked that 15 remittancecompanies are 402 employees.The sampling technique use would be purposive sampling.Primary data would collect by use of questionnaires which are administered through drop andpick method. Data screening would be done to identify any missing data and it would be furthertest for reliability and normality. Data would be analyzing using SPSS version.The studyrecommended that there is need for the remittance companies in Mogadishu to increase theircontrol environment; risk assessment and control activity as it was founded that these variablespositively affects the organizational performance of remittance companies in Mogadishu.